Personal data of employee and its protection - Вишновецький, Вадим Михайлович; Якуненко, Валерія Євгенівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is dedicated to the problems with personal data category definitions, its storage, processing, and protection.The authors point out the main international and domestic regulations, which include fundamental concepts of personal data; above mentioned include regulations of UN, International Labour Organization, Council of Europe, European Union. In order to clarify the human rights guaranteed by 32 Article of Constitution of Ukraine and for determination of enactment means on 1st of June 2010 the Verkhovna Rada of Ukraine has passed the Law of Ukraine “On Personal Data Protection”, the Law came into effect on 1st of January 2011. According to the Law personal data is the information or set of information about the individual, who is identified or may be identified specifically. The conclusion was made, that the personal data of employee is an information or a set of information about an employee, which is reflected in personnel documents. Data about an employee, reflected in a personnel documents, including the age, date and place of birth, place of residence, id number, social status, privileges according to legislation (single mothers, women with children under three years old, Chornobyl beneficiaries, under aged citizens, retired citizens, etc.), in terms of the Law of Ukraine “On Personal Data Protection” is considered the personal data, which compiles the personal data base and there of. A part from this, documentation of an enterprise, institution and organization, existing in electronic or/and paper form, which any how include structured personal data of employees is also considered the personal data base or a part of it. Authors point out that “personal data of an employee” is more specific concept than the “personal data of an individual”, since it takes into account not all the information (facts, events, circumstances of life of an individual), but only the limited information which may characterize the individual as an employee working under employment contract with an employer.